Improving Language Abilities of Children with Autism Using Visual Therapy Approach - Novita, Kholifatul; Sunardi, Sunardi (International Conference on Elementary Education, 2021)
Complex difficulties in communication, social interaction, and language of children with autism are a challenge for parents and teachers to teach them. For example, language difficulties will have an impact on all aspects such as cognitive, physical motor, perception, and several other aspects because language is a parameter in children's development. The purpose of this study was to determine the effect of visual therapy using a picture-word card approach on the language development of children with autism. The subjects in this study are three children with autism. The research method used in this study is a pre-experimental design with pre and post-test without control where children's language was measured before and after being treated, namely by visual therapy. The results of the study using tests before and after treatment experienced a significant increase, so, it can be concluded that visual therapy with picture word cards affects improving children's language with an average difference after 85> 55.